2020
DOI: 10.2319/082819-558.1
|View full text |Cite
|
Sign up to set email alerts
|

Force magnitude as a variable in maxillary buccal segment intrusion in adult patients with skeletal open bite:

Abstract: Objectives To compare the effects of two different force magnitudes on maxillary posterior segment intrusion using mini-screws. The null hypothesis was that there would be no difference between the two force magnitudes. Materials and Methods Adult patients with skeletal open bite and a dental open bite ranging from 3 to 8 mm were recruited for this trial. The comparator group had 200 g of intrusive force applied for posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Other clinical studies reported no difference in intrusion effectiveness or root resorption between 200 g and 400 g intrusion force when using infrazygomatic palatal or buccal miniscrews to intrude buccal segments for anterior open bite cases ( 66 , 67 ).…”
Section: Resultsmentioning
confidence: 97%
“…Other clinical studies reported no difference in intrusion effectiveness or root resorption between 200 g and 400 g intrusion force when using infrazygomatic palatal or buccal miniscrews to intrude buccal segments for anterior open bite cases ( 66 , 67 ).…”
Section: Resultsmentioning
confidence: 97%
“…Some studies utilized miniscrews as the anchorage method. 5 , 15 , 18 Abdulnabi et al 5 used bite plates and coil springs to apply a force of 250 g, whereas Akl et al 18 applied forces of 400 g and 200 g with four coil springs. Kim et al 15 did not report the method of force application but reported an intrusion time of 9.7 months and an intrusion amount of 2.2 mm.…”
Section: Resultsmentioning
confidence: 99%
“…A prior sample size was calculated on the basis of the findings of a previous study [24] for cephalometric analysis of skeletal open-bite patients using the t-test. The analysis was performed using G*Power 3.1 software (Heinrich Heine University, Dusseldorf, Germany) with the power of the statistical test, and the error probability was set at 80% and 0.05.…”
Section: Discussionmentioning
confidence: 99%